Determination of Nine Heavy Metals by Inductively Coupled Plasma Mass Spectroscopy in Groundwater from Northeast Rural of China - Rui, Yu-Kui; Hao, Jing (Asian Journal of Chemistry, 2012)
The safety of drinking water is dangered by many factors, especially groundwater surounding animal breeding waste and toilet. Nine heavy metals in drinking water from northeast rural of China were determined by inductively coupled plasma mass spectroscopy (ICP-MS.) The results showed that ICP-MS for detecting heavy metals simultaneously is accurate and precise. Drinking water (groundwater) from northeast rural of China often exceed the limits of drinking water sanitary standard, especially the content of Mn and Fe. The construction scheme of drinking water project was optimized, scientifically planning water projects, increasing rural water supply project, strengthening the monitoring of water quality and the protection of water sources, preventing rural water pollution, innovating safety management system of rural drinking water, perfecting the supervisory system of rural drinking water and actively studying the safety of rural drinking water.